Description of Stalin’s Period Architecture in the Soviet Union - Apele, Diāna (ARTS AND MUSIC IN CULTURAL DISCOURSE. Proceedings of the International Scientific and Practical Conference, 2014)
In the history of architecture a majority of researchers chronologically distinguish the term “Stalin’s architecture” from the mid 1930’s to the mid 1950’s. However, the author of the article has chosen the period from the 1950’s to 1960’s because in the further research the selected object shall be the Centre of Culture and Education in Rezekne (former cinema “Zvaigzne”) which was launched only in 1957 and which is an outstanding example of socialistic realism of that time in the architecture of Latvia. The article deals with the implementation of the totalitarian system and its ideology in architecture. The article does not provide detailed and multifaceted analysis of totalitarism – its aim is to explore and analyse the brightest samples of architecture in Moscow, the capital of the Soviet Union, and the Soviet Socialistic Republic of Latvia in the 1950’s and 1960’s during the period of socialistic realism. The methods applied in the research are based on the exploration of scientific and publicistic materials revealing the evidence of the respective period in architecture.